Venom Immunotherapy and Aeroallergen Immunotherapy: How Do Their Outcomes Differ? - Incorvaia, Cristoforo; Ridolo, Erminia; Mauro, Marina; Pucciarini, Francesco; Heffler, Enrico; Canonica, Giorgio Walter (Frontiers in Allergy, 2022)
Allergen immunotherapy (AIT) and venom immunotherapy (VIT) are meant to work on the causes of allergies, respectively to respiratory allergens and Hymenoptera venom, inducing tolerance to the allergens and modifying the natural history of allergy. Both types of immunotherapies have evidence of efficacy, but actually they present wide differences in both effectiveness and safety. Indeed, as far as the effectiveness of VIT is concerned, if the protection against fatal reactions to stings is considered as the primary objective, more than 40 years of clinical practice demonstrate complete success. The clinical success of AIT is measurable on the basis of reduction or disappearance of allergic symptoms. The difference between the two treatments is even higher as regards safety: AIT has been concerned in the past by a series of fatal reactions caused, which underwent a progressive decrease when it was understood that they were related to the presence of uncontrolled asthma. However, fatal reactions related to failure to recognize the presence of risk factors or administration errors are still reported. Similarly to what has been observed for efficacy, VIT has never been affected by fatal reactions to the administration of venom, and the most important risk of anaphylaxis, which is the concomitance of mastocytosis, is now identified by measuring its marker serum tryptase. To date, mechanisms of hypersensitivity reactions that differentiate respiratory allergy from Hymenoptera venom allergy have not been successfully demonstrated. We have examined the past and present literature in order to propose reasonable hypotheses about the mechanisms actually involved.